Multilingual plagiarism detection corpus - Juričić, Vedran; Bosanac, Siniša; Štefanec, Vanja (2012)
The paper presents a system for generating multilingual corpuses that can be used to determine performance of plagiarism detection systems.
Projekt MZOS
ENG